1998
DOI: 10.3109/02652049809006868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poly(vinylpyrrolidone) and ethylcellulose on alginate microspheres prepared by emulsification

Abstract: Calcium alginate microspheres were prepared by an emulsification process. The effects of two co-polymers, namely poly(vinylpyrrolidone) and ethylcellulose, on the properties of the microspheres were studied. Microspheres prepared with and without poly(vinylpyrrolidone) were spherical and discrete. The microspheres containing poly(vinylpyrrolidone) exhibited a better flow property but the drug content was lower and the drug release rate higher. The method of incorporating poly(vinylpyrrolidone) was found to (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Ironcross-linked hydroxamated alginic acid has proved to be successful in prolonging drug release of a number of compounds (27). The drug release profiles of calcium alginate microspheres loaded with sulfaguanidine were affected by addition of various copolymers (28,29). It was demonstrated that some cellulose derivatives produced a marked aggregation of the microspheres.…”
Section: Diffusion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ironcross-linked hydroxamated alginic acid has proved to be successful in prolonging drug release of a number of compounds (27). The drug release profiles of calcium alginate microspheres loaded with sulfaguanidine were affected by addition of various copolymers (28,29). It was demonstrated that some cellulose derivatives produced a marked aggregation of the microspheres.…”
Section: Diffusion Systemsmentioning
confidence: 99%
“…It was demonstrated that some cellulose derivatives produced a marked aggregation of the microspheres. Of the cellulose derivatives only ethyl cellulose and hydroxypropyl cellulose resulted in a decrease in drug release rate (28)(29)(30)(31). For these preparations the retardation in drug release was attributed to the aggregate formation.…”
Section: Diffusion Systemsmentioning
confidence: 99%
“…[51] 13-Magnetic microspheres carriers of contraceptive has been designed responsive to the changes in steroid secretions during menstrual cycle. [52] www.wjpps.com Vol 6, Issue 9, 2017. 108…”
Section: Farah World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Magnetic microspheres carriers of contraceptive has been designed responsive to the changes in steroid secretions during menstrual cycle [50].…”
Section: Applications Of Magnetic Microspheresmentioning
confidence: 99%